THE INFLUENCE OF SERVICE QUALITY, CUSTOMER TRUST, AND WORD OF MOUTH ON TRANS BANYUMAS USER DECISIONS - Siti Rahayu; Herni Justiana Astuti; Fatmah Bagis; Restu Frida Utami (Politeknik Negeri Ambon, 2026)
Introduction: Public transportation plays a vital role in supporting people’s mobility, particularly amid growing competition from technology-based services. Trans Banyumas is here to provide modern, comfortable, and affordable public transportation. However, there are still obstacles related to the perception of service quality, trust level, and the effectiveness of word-of-mouth that can affect user decisions. This study will examine how the influence of service quality, customer trust, and word-of-mouth communication affects people’s decisions about using Trans Banyumas.Methods: This research uses a quantitative, associative approach. The sample size was 159 respondents, selected using purposive sampling criteria, including those who had used Trans Banyumas in the last three months. Data were collected through live and online questionnaires and then analyzed using multiple linear regression in SPSS version 27.Results: The analysis findings indicate that service quality, customer trust, and word of mouth have a positive and significant impact on user decisions. The conclusion of these findings confirms that consistently improving service quality, strengthening trust, and optimizing user recommendations are effective strategies to encourage decisions to use Trans Banyumas. Keywords: Customer Trust, Service Quality, Word of Mouth, User decision